Microstructural analysis of ZnO-CuPc nanocomposites synthenised by hydrothermal method - Hamad, Rekawt Khdir; Canbay, Canan Aksu; Özkul, İskender (Murat Yakar, 2021)
With the discovery of inorganic semiconductors, silicon and germanium became very important materials in the field of electronics. The use of these materials with these limited features for a long time has become insufficient in the face of increasing demands. For this reason, organic semiconductors have revolutionized structures that respond to these demands. In this study, we synthesized ZnO based semi-material with the hydrothermal method. Structural characterizations were made by XRD, SEM (EDX) and FTIR. © 2021, Murat Yakar. All rights reserved.
Keywords: Composite; EDX; Hydrothermal method; SEM; Structural characterization; XRD